Orientation of Tribolium castaneum (Herbst) (Coleoptera: Tenebrionidae) adults at various distances to different concentrations of aggregation pheromone 4, 8-dimethyldecanal. (May 2020) - Dissanayaka, D.M.S.K.; Sammani, A.M.P.; Wijayaratne, L.K.W.
Abstract: Tribolium castaneum is a serious pest of durable agricultural commodities during storage. The male T. castaneum adults release the aggregation pheromone 4, 8-dimethyldecanal (4, 8 DMD). The 4, 8 DMD is produced commercially and available to be used in Dome traps along with their recommended kairomone but low trapping response is often reported. Concentration of 4, 8 DMD influences the attraction of T. castaneum adults but its intensity may vary under different warehouse settings. Further, the orientation response of T. castaneum adults from different distances to the synthetic 4, 8 DMD is still uncertain. Therefore, the objective of this research was to evaluate the effect of distance to the traps having different 4, 8 DMD concentrations on the orientation response of T. castaneum adults. The dome trap having two pheromone septa and kairomone was placed inside the experimental arena. From pheromone, different concentrations were used. One-month-old T. castaneum adults were individually marked and released from different distances at the same time. The adults reached the trap were counted 4 h following release. Alternatively the experiment was repeated without having the kairomone inside the trap. One trap having neither the pheromone nor kairomone (empty trap alone) and one having hexane only were used as controls. For all the pheromone concentrations used, the maximum trapping percentage was found when the beetles were released at 30 cm or 60 cm from the pheromone. Further, the highest trapping percentage was given by 0.5 μL of 4, 8 DMD. At a given distance, the traps having pheromone+kairomone better attract T. castaneum adults than those had only the pheromone. The study concludes that the degree of attraction of T. castaneum adults varies with the distance from the trap and the trap composition. Further studies are required to test the efficacy of 4, 8 DMD and kairomones under real warehouse settings. Highlights: Attraction of Tribolium castaneum released different distances from traps was determined. Trapping percentage differed with the pheromone concentration and the distance of release. Presence of kairomone with the pheromone inside the trap enhances trapping percentage.